Mejoramiento del frijol por introduccion y seleccion - Voysest Voysest, Oswaldo (United Nations Development Programme, 1985)
The most important steps in the introduction and selection of bean genetic material are described. The 1st step involves the identification of the existing sources of germplasm (germplasm banks, national and international nurseries, lines obtained through hybridization, and local materials) and the selection and introduction of those materials that fulfill the breeding objectives and that, in general terms, respond to marketing conditions and farmers' demands. The 2nd step involves the establishment of discriminatory trials to discard deficient materials and to select the best. These trials can be of 4 types: observation or preliminary trials, yield trials, adaptation or regional trials, and on-farm trials. During the last step promising lines are multiplied and registered. (CIAT)